Control of Electron‐transfer in Immunonanosensors by Using Polyclonal and Monoclonal Antibodies. Issue 8 (14th January 2016) - Mars, Abdelmoneim; Parolo, Claudio; de la Escosura‐Muñiz, Alfredo; Raouafi, Noureddine; Merkoçi, Arben
Abstract: The design and operation of biosensors is not trivial. For instance, variation in the output signal during monitoring of analytes can not usually be controlled. Hence, if such control were possible, and could be triggered on demand, it would greatly facilitate system design and operation. Herein, we report the design of two types of voltamperometric immunosensors, in which the magnitude of the current output signal (differential pulse voltammetry [DPV]) can be increased or decreased as needed. The designed systems use monoclonal and polyclonal anti‐human IgG antibodies, conjugated to monopodal ferrocene‐modified gold nanoparticles that are casted onto screen‐printed carbon electrodes (Ab/mFcL/AuNPs/SPCEs). Upon addition of human IgG as antigen, the systems exhibit opposite responses according to the Ab: the current decreases when monoclonal Ab is used, whereas it increases when polyclonal Ab is used. We attributed the former response to inhibition of electron‐transfer (due to the formation of a protein layer), and the latter response, to a global increase in electron transfer (induced by the aggregation of gold nanoparticles). These effects were confirmed by studying a custom‐made lipoic acid‐based bipodal ligand, which confirmed that the increase in current is effectively induced by the aggregation of the modified nanoparticles (pAb/mFcL/AuNPs). Both sensors have large dynamic ranges, although the pAb‐based one was found to be 3.3‐times more sensitive. Tests of selectivity and specificity for ovalbumin, α‐lactalbumin and serum bovine albumin showed that the immunosensors are highly selective and specific, even in the presence of up to 1000‐fold levels of potentially competitive proteins. The limit of detection for human IgG using the pAb/mFcL/AuNP bioconjugate was estimated to be 0.85 ng/mL. The pAb/mFcL/AuNPs‐based biosensor has used to determine amounts of human IgG in real sample. Abstract :